Implementing Project-Based Learning for Improving Literacy in Madrasah Ibtidaiyah - Aulannisa, Farah (JURNAL IJ-ATL, 2022)
This study aims to describe the steps of implementing project-based learning methods in developing students' reading skills and to measure the effectiveness of this method in improving reading comprehension among eleventh grade students. This study is based on the need for innovative methods that can improve students' literacy skills, especially in teaching Arabic at the secondary school level. The research approach uses a quantitative method with an experimental design, involving a control group and an experimental group. Data were collected through observation, interviews, questionnaires, documents, and tests, then analyzed using SPSS 25 statistical tools and a Likert scale for the questionnaire results. The results of the study showed that project-based learning was significantly effective in improving students' reading comprehension. This is indicated by the significant difference between the pre-test and post-test results in the experimental group compared to the control group. These findings are expected to be a reference for educators in implementing project-based learning strategies in various educational contexts.